Memutus Mata Rantai Radikalisme dan Terorisme dengan Mengedepankan Kegiatan Positif di Sekolah - Marjan Miharja; Riyanta Riyanta; Fandy Lucky S.; Ali Aridi; Arby Hermawan; Agung Ardiansyah; Panji Adela; Fatih Fauzan Zulfa R.; Lisda Purwanti; Wira Agustian Tri H.; Sonia Yolla Viqwan; Muhammad Mursid; Esa Dian Arifni (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Efforts to combat radical movements to terrorism of any kind, should not be carried out by violent means, as the United States has done to Afghanistan. This is because the violence will only add to the violence of the new volume. Volumes of crimes against humanity against innocent civilians. We can't quell the impossibility with the impossibility. Efforts to counter terrorism must start from uprooting the root or source of the problem. On the domestic political stage, the rise of religious radicalism movements is marked by the rise of mass actions driven by several hardline Islamist groups, which generally have something in common in one respect, namely; want the grounding or application of Islamic law in the archipelago. . Efforts to counter terrorism must start from uprooting the root or source of the problem. The most important root or source of acts of terrorism today is to remove injustice and lameness in the order of international relations. It needs intense dialogue between the warring parties in order to truly find the best solution to end the conflict